2021
DOI: 10.13048/jkm.21023
|View full text |Cite
|
Sign up to set email alerts
|

Statistical Analysis of Outpatients Trends at Korean Medicine Hospitals of Daejeon University by Region before and after COVID-19

Abstract: Objectives: This study is designed to statistically analyze data of outpatients visiting for recent 3 years. The purpose is to identify tendencies of patients who visit the hospitals before and after COVID-19. Methods: This study retrospectively analyzed the medical records of 452,487 patients who visited to the Daejeon·Cheonan·Cheongju Korean Medicine Hospital of Daejeon University from January 1, 2018 to August 31, 2020. The data is classified according to year, month, gender, age, and visit type. The statis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Large decreases were recorded in the number of patients using Korean medicine (decreased by 12.5%) after the outbreak of COVID-19 [4]. For example the number of first-time patients visiting the Department of Acupuncture and Moxibustion at the Korean medicine hospital in Daejeon decreased by 15.2% [21]. We also demonstrated that the series of COVID-19 waves did not overlap with the timing of decline in patient numbers by month.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Large decreases were recorded in the number of patients using Korean medicine (decreased by 12.5%) after the outbreak of COVID-19 [4]. For example the number of first-time patients visiting the Department of Acupuncture and Moxibustion at the Korean medicine hospital in Daejeon decreased by 15.2% [21]. We also demonstrated that the series of COVID-19 waves did not overlap with the timing of decline in patient numbers by month.…”
Section: Discussionmentioning
confidence: 71%
“…The Korea Institute of Oriental Medicine published the results of its survey titled "Utilization of Korean Medicine and Consumption of Korean Medicine" in 2020 [20]. Several studies reported the trends of patients visiting Korean medicine hospitals before and during the COVID-19 pandemic [21][22][23]. However, to the best of our knowledge, no previous study has investigated patients visiting a Korean medicine hospital for a single disease, including facial palsy.…”
Section: Introductionmentioning
confidence: 99%